2018
DOI: 10.1108/hff-08-2016-0297
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of thermodynamic models for ice accretion on airfoils

Abstract: Purpose This paper aims to assess the strengths and weaknesses of four thermodynamic models used in aircraft icing simulations to orient the development or the choice of an improved thermodynamic model. Design/methodology/approach Four models are compared to assess their capabilities: Messinger, iterative Messinger, extended Messinger and shallow water icing models. They have been implemented in the aero-icing framework, NSCODE-ICE, under development at Polytechnique Montreal since 2012. Comparison is perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Many methods have been developed for this approach, most notably the Messinger Model, Extended Messinger Model, Iterative Messinger Model, or Shallow Water Icing Model (SWIM). A comparative assessment of these models can be found in [25]. Finally, for the conjugate heat transfer solver, the effect of the internal heat generated by a thermal IPS is transferred to the mass and energy balance equations by a conductive heat transfer term.…”
Section: Background and Inspirationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many methods have been developed for this approach, most notably the Messinger Model, Extended Messinger Model, Iterative Messinger Model, or Shallow Water Icing Model (SWIM). A comparative assessment of these models can be found in [25]. Finally, for the conjugate heat transfer solver, the effect of the internal heat generated by a thermal IPS is transferred to the mass and energy balance equations by a conductive heat transfer term.…”
Section: Background and Inspirationmentioning
confidence: 99%
“…Together with the steady-state icing approach, these assumptions neglect the effects of surface roughness as well as the water and ice thickness on the airfoil surface. While these assumptions have been used in past works and provided acceptable results [25,30], they are known to produce inaccuracies and errors in the predicted ice shape. For the simplified nature of this work, and since the icing analysis is only focused on the stagnation point, the results may be acceptable.…”
Section: The Icing Thermodynamic Modelmentioning
confidence: 99%
“…This manufactured geometry was first presented in [21] and is generated from a NACA0012 airfoil with added artificial ice near the leading edge. The three-horn configuration was selected to obtain multiple flow recirculation zones and create a difficult situation for the ice growth solver because of the presence of highly concave and convex features.…”
Section: A Manufactured Ice Shapementioning
confidence: 99%
“…Once the heat transfer along the flat plate is known, the ice accretion simulations can be performed. To compute the 2D ice accretions, the Messinger approach is used [6,7]. The basis of this approach is to compute the ice growth rate in a control volume using a mass and an energy balance.…”
Section: Ice Accretion Modelmentioning
confidence: 99%
“…Most of the icing codes used to predict the ice accretion shape are based on the Messinger model [6]. The model uses a mass and energy balance involving the convective heat transfer to compute the ice growth on the airplane surface [7]. Past studies have shown that the convective heat transfer, modeled by a convective heat transfer coefficient, has a major impact on the final shape of the ice accretion [8,9].…”
Section: Introductionmentioning
confidence: 99%